The Islamic concept of green organizational leadership model: a preliminary development - Abdul Aziz, Siti Fardaniah; Selamat, Mohd Nasir; Ibrahim, Anesee; Mohamed Makhbul, Zafir Khan; Che Kassim, Arena; Wati Halim, Fatimah; Mukapit, Mukhiffun; Zakaria, Ummi Kalsom (Human Resource Management Academic Research Society, 2022)
Previous researchers find that the existence of green organizations is very important as it not only can overcome environmental pollution but also has a positive impact on organizational management by helping to reduce costs, increasing profitability, and overcoming global competition. Hence, the need to create green organizations is becoming more critical because of the increase in worldwide environmental pollution including the air, water, and sound pollution. Fortunately, previous researchers also find that green organizational leadership is the key to create successful green organizations. However, green organizational leadership from Islamic perspective have not been discussed yet although researchers have predicted that most of the human population in the worldwide are estimated to be Muslims by the year 2070. Hence, this paper aims to develop the Islamic Concept of Green Organizational Leadership Model (ICGOLM) as a new model that can be referred to develop green organizational leaders from Islamic perspective. Using literature review, the ICGOLM hypothesized that green climate psychology mediates the relationship between Islamic concept of green organizational leadership (ICGOL) and strategic green behaviour. Additionally, the ICGOL comprises six competencies including the intellectual, professional, moral, social, emotional, and Islamic competencies. The model is beneficial to develop action plan and intervention, government policy and rules, and initiative to create successful green organization especially in Muslim countries. However, the ICGOLM model should be tested further using empirical study.